To solve the system of equations given by:
- \( 4h + 4s = 10 \)
- \( 7h + 5s = 15 \)
we will follow these steps:
Step 1: Simplify the first equation
From the first equation, we can simplify it by dividing each term by 4:
\[ h + s = 2.5 \]
Step 2: Express one variable in terms of the other
We can express \( s \) in terms of \( h \) from this simplified equation:
\[ s = 2.5 - h \]
Step 3: Substitute into the second equation
Next, substitute \( s \) into the second equation:
\[ 7h + 5s = 15 \]
Replacing \( s \):
\[ 7h + 5(2.5 - h) = 15 \]
Step 4: Distribute and combine like terms
Calculating inside the parentheses:
\[ 7h + 12.5 - 5h = 15 \]
Combine like terms:
\[ 2h + 12.5 = 15 \]
Step 5: Solve for \( h \)
Now, subtract 12.5 from both sides:
\[ 2h = 2.5 \]
Now divide by 2:
\[ h = 1.25 \]
Step 6: Solve for \( s \)
Now substitute \( h \) back into the equation for \( s \):
\[ s = 2.5 - h = 2.5 - 1.25 = 1.25 \]
Final Answer:
Thus, the cost of a hot dog \( h \) and the cost of a soda \( s \) are both:
\[ h = 1.25 \quad \text{(cost of hot dog)} \] \[ s = 1.25 \quad \text{(cost of soda)} \]
In decimal form, the solutions are:
Cost of hot dog: $1.25
Cost of soda: $1.25